Cx43 suppresses evx1 expression to regulate joint initiation in the regenerating fin. Issue 9 (12th July 2017) - Dardis, Gabrielle; Tryon, Robert; Ton, Quynh; Johnson, Stephen L.; Iovine, M. Kathryn
Abstract : Background : How joints are correctly positioned in the vertebrate skeleton remains poorly understood. From our studies on the regenerating fin, we have evidence that the gap junction protein Cx43 suppresses joint formation by suppressing the expression of the evx1 transcription factor. Joint morphogenesis proceeds through at least two discrete stages. First, cells that will produce the joint condense in a single row on the bone matrix ("initiation"). Second, these cells separate coincident with articulation of the bone matrix. We propose that Cx43 activity is transiently reduced prior to joint initiation.Results : We first define the timing of joint initiation with respect to regeneration. We next correlate reduced cx43 expression and increased evx1 expression with initiation. Through manipulation of cx43 expression, we demonstrate that Cx43 negatively influences evx1 expression and joint formation. We further demonstrate that Cx43 activity in the dermal fibroblasts is required to rescue joint formation in the cx43 mutant, short fin b123 .Conclusions : We conclude that Cx43 activity in the dermal fibroblasts influences the expression of evx1, and therefore the differentiation of the precursor cells that give rise to the joint‐forming osteoblasts. Developmental Dynamics 246:691–699, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: A time line for the initiation of joint formation during fin regeneration was established. Manipulation of Cx43 levels is negatively correlated with evx1 expression and with joint formation, consistent with our model that Cx43 must be abrogated for joint formation to occur. Cx43 function in dermal fibroblasts is responsible for both Cx43‐dependent regenerate length and Cx43‐dependent suppression of joint formation.